KETAHANAN API KAYU SENGON (Paraserianthes falcataria (L.) Nielsen) YANG DIAWETKAN DENGAN BAHAN PENGAWET BORAKS: Fire Resistance Of Sengon (Paraserianthes Falcataria (L.) Nielsen) Preserved With Borax - IRVIN DAYADI (Forestry Faculty of Universitas Hasanuddin, 2021)
Woods are easy to ignite by fire. Increasing fire resistance with fire retardants is needed to increase safety and reduce losses due to fire. This research aimed to determine the fire resistance of Sengon wood treated with preservation of borax with a concentration of 5%, 10%, and 15% by cold immersion for five days. The fire resistance test used the ASTM E69-02 standard, while the statistical analysis (ANOVA) of the test data used a Completely Randomized Design at the 95% confidence level and the LSD test (Least Significant Difference test). The results showed of the physical properties of Sengon wood, the average value of air-dry moisture content was 14.08%, air-dry density was 0.33g/cm3, and oven-dry density was 0.30g/cm3. In contrast, the LSD test showed a significant difference between the controls to the all-borax preservation treatments, but between 5%, 10%, and 15% borax treatments were not significantly different. The best fire resistance parameter values ​​were found in the 15% borax treatment, with the retention of 38.04 kg/m3, burning intensity 12.58%, combustion time 437.5 seconds, and effectiveness of 4.76. The fire resistance effectiveness value of all equipment cannot meet the ASTM E69-02 standard